Penyelesaian Sengketa Perbankan Syariah Perspektif UUD Nomor 21 Pasal 55 Tahun 2008 dan Istishlah - Fathoni, M. Kamal; Sasnifa, Pidayan; Burhanuddin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Disputes are a natural thing and often occur in shariah banking, but it is not always caused by banking errors, but also customer errors. This study aims to reveal two main things, namely: (1) to find out how the application of UU No. 21 Tahun 2008 on Sharia Banking Dispute Settlement, (2) to find out how to resolve Sharia Banking Disputes according to istishlah. The approach used is qualitative which is descriptive. Based on the research conducted by the author, the results of the conclusion that: 1) In determining a case, the Religious Court looks at it from the point of view of the Law (Preferred), Sharia principles and also what cases the plaintiff experienced. If there is a dispute that does not meet the criteria in the Constitution, it will be immediately rejected. 2) Istishlah is a view that is more inclined to choose a middle ground of a problem so as not to cause harm to people. If there is a problem that cannot be resolved due to a dispute in the banking of shariah, in the religious court because the problem does not meet the requirements described in the constitution, the problem can be resolved through deliberation, as-sulh, tahkim, hisbah, and judicial channels (qadha).